2016
DOI: 10.3390/molecules21111424
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Formula HT048 Attenuates Diet-Induced Obesity by Improving Hepatic Lipid Metabolism and Insulin Resistance in Obese Rats

Abstract: Abstract:It is well established that obesity causes a variety of chronic diseases such as cardiovascular diseases and diabetes. Despite the diligent scientific efforts to find effective ways to lower the level of obesity, the size of obese population grows continuously around the world. Here we present the results that show feeding diet containing HT048, a mixture of the extracts of Crataegus pinnatifida leaves and Citrus unshiu peel, two of the well-known traditional herbal medicines in Eastern Asia, decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…The above changes were attenuated with SJP treatment. In accordance with the present study, numerous studies have demonstrated similar changes in high-fat diet induced obesity and Traditional Chinese herb showed a great potential to improve obesity-induced inflammatory injuries via ameliorating inflammation response [ 36 , 37 ], modulating microbiota hemostasis [ 38 , 39 ] and lipid metabolism [ 40 43 ], and attenuating insulin resistance [ 44 ]. In a part of the above-mentioned Chinese herb formula, we found similar ingredients in SJP, such as rhein [ 38 ] and Curcuma longa [ 40 ], which might be the main effective constituent of the classic formula.…”
Section: Discussionsupporting
confidence: 86%
“…The above changes were attenuated with SJP treatment. In accordance with the present study, numerous studies have demonstrated similar changes in high-fat diet induced obesity and Traditional Chinese herb showed a great potential to improve obesity-induced inflammatory injuries via ameliorating inflammation response [ 36 , 37 ], modulating microbiota hemostasis [ 38 , 39 ] and lipid metabolism [ 40 43 ], and attenuating insulin resistance [ 44 ]. In a part of the above-mentioned Chinese herb formula, we found similar ingredients in SJP, such as rhein [ 38 ] and Curcuma longa [ 40 ], which might be the main effective constituent of the classic formula.…”
Section: Discussionsupporting
confidence: 86%
“…This method comes into play when lifestyle interventions fail to achieve the desired weight reduction and previous studies recommended that this method should be initiated concomitantly with lifestyle modifications (Christopher and Kumar, 2009; Ferrier, 2014; Yoon et al, 2016). Following the recommendation by the Endocrine Society Clinical Practice Guideline for the pharmacological treatment of obesity, this method is to be used only for patients that have a BMI > 30 or have a BMI ≥ 27 but with comorbidity (Apovian et al, 2015; Nan-Nong et al, 2016).…”
Section: Pharmacotherapy/drug Therapymentioning
confidence: 99%
“…The effects were supported one year later when it was demonstrated that HT048 decreased body and total white adipose tissue weight and serum insulin levels in HFD-fed obese rats, whereas at the molecular level the supplement downregulated genes involved in lipogenesis, gluconeogenesis, and adipogenesis, and up-regulated β-oxidation genes. In addition, no interactions were observed between HT048 supplementation and orlistat drug, which was also used in the study (Lee et al, 2016). Orlistat and C. monogyna ethanolic extracts significantly lowered the hypercholesterolemia-increased serum level of hepatic enzymes and lipid peroxidation level in the hypercholesterolemia-induced oxidative stress in rats, protected from hepatic thiol depletion, and improved lipid profile and hepatic damages (Rezaei-Golmisheh et al, 2015).…”
Section: Hypoglycemic Effectsmentioning
confidence: 99%